Individual and Contextual Factors Influencing Special Education Teacher Learning in Literacy Learning Cohorts. (February 2014) - Brownell, Mary T.; Lauterbach, Alexandra A.; Dingle, Mary P.; Boardman, Alison G.; Urbach, Jennifer E.; Leko, Melinda M.; Benedict, Amber E.; Park, Yujeong
In this study, researchers operated from cognitive and situated perspectives to understand how individual qualities and contextual factors influenced elementary special education teachers' learning in a multifaceted professional development (PD) project, Literacy Learning Cohort, focused on word study and fluency instruction. Grounded theory methodology was used to analyze qualitative interviews, cohort meetings, and classroom observations. Participants included five special educators who taught reading to students with disabilities in Grades 3 to 5. Results highlighted the central role of teachers' ability to analyze their current instructional practice in developing integrated knowledge of word study and fluency instruction and crafting more integrated instruction. Teachers' individual qualities, contextual factors, and PD components also worked in concert with teachers' propensity to analyze instruction and ultimately influenced teacher learning (i.e., degree of integrated knowledge and practice demonstrated). Implications of these findings for designing effective PD efforts are discussed.